2017
DOI: 10.1017/jfm.2017.471
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of a neutrally buoyant suspension column: from Newtonian to apparent non-Newtonian flow regimes

Abstract: Experiments on the collapse of non-colloidal and neutrally buoyant particles suspended in a Newtonian fluid column are presented, in which the initial volume fraction of the suspension $\unicode[STIX]{x1D719}$, the viscosity of the interstitial fluid $\unicode[STIX]{x1D707}_{f}$, the diameter of the particles $d$ and the mixing protocol, i.e. the initial preparation of the suspension, are varied. The temporal evolution of the slumping current highlights two main regimes: (i) an inertial-dominated regime follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…2(a)], the liquid-grain column remains static after the sluice gate is opened (even after several hours). This observation has already been reported in the case of a neutrally buoyant suspension, with a = 1, φ > 0.61, and d < 230 μm [23]. This configuration will FIG.…”
Section: A the Different Flow Regimes In A Water-saturated Casesupporting
confidence: 75%
See 2 more Smart Citations
“…2(a)], the liquid-grain column remains static after the sluice gate is opened (even after several hours). This observation has already been reported in the case of a neutrally buoyant suspension, with a = 1, φ > 0.61, and d < 230 μm [23]. This configuration will FIG.…”
Section: A the Different Flow Regimes In A Water-saturated Casesupporting
confidence: 75%
“…Other configurations share some similarities with the present liquid-saturated granular column, namely, the slumping of a neutrally buoyant suspension [19][20][21][22][23] and the fully immersed granular collapse [24][25][26][27][28][29][30]. In the first case, the density of the interstitial fluid and that of the grains is similar and hence the granular pressure is canceled.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Additionally, in the case of dam-break flows on a horizontal plane, it is well known that a value of = 2 is hardly reached due to bottom shear dissipation, which becomes significant in regions where the depth of the current becomes small, particularly close to the front (Dressler, 1952;Hogg & Woods, 2001;Hogg & Pritchard, 2004). In the literature, the parameter is usually found in the range = [1 ∶ 2] (Bonometti et al, 2008(Bonometti et al, , 2017Dressler, 1954;Jánosi et al, 2004;Leal et al, 2006;Roche et al, 2008), according to the value = 1.4 obtained here. Similar conclusions can be drawn from the inset of Figure 3a.…”
Section: Control Parametersmentioning
confidence: 99%
“…For tall grain columns (a 3), Larrieu, Staron & Hinch (2006) have shown that the dynamics can be understood from depth-averaged shallow-water equations applied to a thin horizontally spreading layer (with basal Coulomb friction), which is fed with vertical 'raining' grains (with no horizontal momentum) from the initial column in free fall. The influence of an ambient fluid on the granular collapse has then been investigated experimentally by Meruane, Tamburrino & Roche (2010), Rondon, Pouliquen & Aussillous (2011), Bougouin, Lacaze & Bonometti (2017) and Bougouin & Lacaze (2018), and numerically by Topin et al (2012). For immersed cases, the Stokes number that measures the importance of grain inertia relative to viscous forces and the solid/fluid density ratio are important dimensionless numbers that control the avalanche regime (Courrech du Pont et al 2003a).…”
Section: Introductionmentioning
confidence: 99%